1998
DOI: 10.1023/a:1006068305454
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The structure of the gene encoding the apoprotein of phytochrome B (PHYB1) in tomato has been determined from genomic and cDNA sequences. In contrast to PHYA, PHYB1 lacks an intron upstream of the first ATG. A single transcription start site was found by 5' RACE at -116. Tomato PHYB1 spans 7 kb starting from the first ATG. The coding region is organized into four exons as for other angiosperm PHY. The deduced apoprotein consists of 1131 amino acids, with a molecular mass of 125.4 kDa. Tomato phytochrome B1 sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…This revealed that the genomic sequence includes four exons (Figure 1B), as also is the case for the PHYB genes present in A. thaliana , potato [19], tomato[20], rice [11], [21] and maize [22] PHYB s. Although the exon lengths in GmPHYB1 were comparable with those in AtPHYB , the soybean introns were considerably larger (Figure 1B). …”
Section: Resultsmentioning
confidence: 56%
“…This revealed that the genomic sequence includes four exons (Figure 1B), as also is the case for the PHYB genes present in A. thaliana , potato [19], tomato[20], rice [11], [21] and maize [22] PHYB s. Although the exon lengths in GmPHYB1 were comparable with those in AtPHYB , the soybean introns were considerably larger (Figure 1B). …”
Section: Resultsmentioning
confidence: 56%
“…The hp2 mutant is deficient for DET1 transcription factor, a negative regulator of light signal transduction (Soressi, 1975). phya, phyb1, phyb2, phyab1, phyb1b2, and phyab1b2 are loss-of-function mutants initially characterized by Kerckhoffs et al (1996); Kerckhoffs, Schreuder, Van Tuinen, Koornneef, and Kendrick (1997); Kerckhoffs et al (1999); Lazarova, Kerckhoffs, et al (1998); Lazarova, Kubota, et al (1998);and Weller, Schreuder, Smith, Koornneef, and Kendrick (2000).…”
Section: Introductionmentioning
confidence: 99%
“…The PHYE amiRNA line, previously characterized phyB1 (Lazarova G. I. et al, 1998a ) and phyB2 (Weller et al, 2000 ) null mutants, and wild-type Moneymaker were characterized for the internode elongation shade avoidance response over time under long day high R:FR and low R:FR to induce the shade avoidance response in a growth chamber. Like phyB2 mutants, PHYE amiRNA plants have wild-type internode lengths in both high R:FR and low R:FR (Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this work and that of others (Weller et al, 2000 ) shows a different role for the tomato phytochrome family members as compared to Arabidopsis. In order to investigate the role of the tomato PHYB family members, we took advantage of the previously characterized phyA (Lazarova G. I. et al, 1998b ), phyB1 (Lazarova G. I. et al, 1998a ), and phyB2 (Weller et al, 2000 ) null mutants and generated an artificial microRNA (amiRNA; Alvarez et al, 2006 ; Schwab et al, 2006 ; Warthmann et al, 2008 ) to knock down expression of PHYE mRNA ( PHYE amiRNA). In this manuscript, we characterize the role of phyE in both internode elongation and shade avoidance and demonstrate that phyE is required for shade avoidance in the absence of phyB1 and phyB2.…”
Section: Introductionmentioning
confidence: 99%